KUALITAS PELAYANAN TOKO MANDIRI ATK DALAMMENINGKATKAN KUALITAS KONSUMEN - Nuriawati; Mohammad Hosen (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2021)
In doing business, there is an action from distributors to consumers that can solve complaints, providesatisfaction, and comfort to consumers it is a service, in a company required quality of service to maintaincompany profile and customer satisfaction. This study aims to determine the quality of service at theMANDIRI ATK Patokan Kraksaan Probolinggo shop in improving consumer quality. This researchmethod uses a qualitative approach, the strategy used is to remember the information needed throughinterviews.Then the researcher is looking for several consumers to become sources but before conductingthe interview the researcher makes observations on the location. Researchers collect information bydocumenting the results of observations and interviews. The quality of service at the MANDIRI ATKshop at the Patokan Kraksaan Probolinggo, prioritizes convenience when the transaction takes place forthe sake of consumer satisfaction. This research is suitable for companies that still do not know how toimprove consumer quality. Because the MANDIRI ATK store has a quality service that is able to providesatisfaction to consumers.